Some reflections on IPv6 adoption in Australia - Dell, Peter; Kwong, C.; Liu, Ying (Emerald, 2008)
IPv6 is an inevitable upgrade to Internet Protocol (IP), the underlying protocol uponwhich the Internet is based, and solves many problems with the existing technologyincluding limited address space, performance and security. Although IPv6 has beensupported by products from major vendors for many years, adoption has beenpractically non-existent. Meanwhile, the Internet continues to grow and the size ofthe problem increases.This unsatisfactory situation is a consequence of network externalities in whichrational individuals have no motivation to be the â€œfirst-moverâ€ . We argue thatgovernment action is required to promote diffusion of IPv6, but note that this isdifficult and may be unlikely in the absence of a business case. Making the case forIPv6 should not be problematic given the range of â€œhiddenâ€ costs of retaining thestatus quo; however, there has been no systematic effort to assess such costs. We thusrecommend a number of directions for future research to address this deficiency